Comparison of gut microbiota structure and Actinobacteria abundances in healthy young adults and elderly subjects: a pilot study - Li, Jun; Si, Haiyan; Du, Haitao; Guo, Hongxia; Dai, Huanqin; Xu, Shiping; Wan, Jun (BMC microbiology, 2021)
The aim was to determine the potential association of the gut microbiota composition, especially the abundance of Actinobacteria, as well as the differentiation of functional and resistance genes with age (young adults vs elderly subjects) in China. The patterns of relative abundance of all bacteria isolated from fecal samples differed between young adults and elderly subjects, but the alpha diversity (Chao1 P = 0.370, Shannon P = 0.560 and Simpson P = 0.270) and beta diversity (ANOSIM R = 0.031, P = 0.226) were not significantly different. There were 3 Kyoto Encyclopedia of Genes and Genomes (KEGG) metabolic pathways (carbon metabolism, inositol phosphate metabolism, and sesquiterpenoid and triterpenoid biosynthesis) and 7 antibiotic resistant genes (ARGs) (macrolide lincosamide-streptogramin B (MLSB), tetracycline, aminoglycoside, sulfonamide, fosmidomycin, lincomycin, and vancomycin) that showed significant differences between the 2 groups (all P < 0.05). The abundance of Actinomycetes was enriched (about 2.4-fold) in young adults. Bifidobacteria dominated in both young adults and elderly subjects, with overall higher abundances in young adults (P > 0.05). Only the Bifidobacterium_dentium species showed significant differences between the 2 groups (P = 0.013), with a higher abundance in elderly subjects but absent in young adults. The present study revealed that there were 3 KEGG metabolic pathways and 7 ARGs as well as enhanced Bifidobacterium_dentium species abundance in elderly compared to young subjects.